NEED AND APPROACH OF PHARMACEUTICAL STANDARDIZATION OF KWATH KALPANA IN PRESENT SCENARIO- A CRITIQUE (International Journal of Ayurveda and Pharma Research, 2016)
Ayurvedic pharmaceutical industries are flourishing now a days demands standardization at every step of pharmaceutical processing. Kwatha (Decoction) is the basic dosage form for most of other important dosage form such as Avaleha (Linctus), Snehapaka (medicated oils and Ghruta), Sandhankalpana (Alcoholic fermentations) etc, hence need standardization at various steps of pharmaceutical processing. Due to difference of opinion among Ancient Acharyas (Faculties) for various pharmaceutical factors such as proportion of water, particle size of raw drugs, duration of heating etc. of kwatha kalpana, large scale manufacturing and polyherbal content of Kwatha, some factors need to be controlled to get standard quality of kwatha. Various pharmaceutical factors affect quality of Kwatha such as Vessel (Earthen, Copper, Stainless still) to be used, temperature(High or Low flame), proportion of water(4, 8, 16 part) to be added, particle size of crude drug(fine or coarse) to be used for Kwatha, duration of heating(1/4 or1/8) and its qualitative and quantitative estimation of phyto constituents using appropriate analytical techniques is the need of Hour, hence the paper discussed need and proper approach for pharmaceutical standardization of Kwatha to optimize the said factors for practicing uniformity in pharmaceutical industries for universal acceptance.